Design of Shell and Tube Heat Exchanger for Production Aluminium Nitride Nanoparticle in Application Industry - Ranggaweny Al-Ghani; Asep Bayu Dani Nandiyanto; Teguh Kurniawan (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The current industrial implementation process is required to be carried out efficiently and environmentally friendly, this can be done with the presence of a heat exchanger. However, heat exchangers in the production of aluminum nitride nanoparticles are still rare. The purpose of this research is to analyze and improve the heat exchanger design in the production process of aluminum nitride nanoparticles at low cost. The heat exchanger can be designed based on several parameters of the TEMA standard by dimensional specification and specifications of hot and cold fluids. The method is calculated using a Microsoft excel application to evaluate the heat exchanger design according to the TEMA standard. The results showed that the shell and tube heat exchanger was designed with 39 tubes and an effective value of 85.72%. These results have met the TEMA standard and it is hoped that the design and evaluation of this heat exchanger can be used as a reference in the aluminum nitride nanoparticle production industry.